Deskripsi Tari Munai Serumpun Mata Kuliah Koreografi Tari Program Studi Pendidikan Seni Pertujukan Universitas PGRI Palembang - Dwi Afriani; Suci Rahmadini (Jurnal Pengetahuan dan Pendidikan, 2024)
This study aims to describe the Munai Serumpun Dance with dance choreography courses in the Performing Arts Education Study Program, PGRI Palembang University. This study uses qualitative methods and observations with various data collection techniques. This work was made to find out the development of the motions of the Munai Serumpun Dance which is based on the Setudung Sedulang dance. The research results show that there are several main issues, including: 1) spatial design, 2) timing and dance accompaniment design, 3) dynamics, 4) dramatic design and 5) group composition.